MENERAPKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS IVB SDN 011 BUKIT GAJAH KECAMATAN UKUI KABUPATEN PELALAWAN - Asriati ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
Based on the experience of researchers teach in class IV student learning outcomes IPS ClassIVB SDN 011 Bukit Gajah Kecamatan Ukui Kabupaten Pelalawan. In SDN 011 Bukit GajahKecamatan Ukui Kabupaten Pelalawan that the results of learning IPS as expected has notbeen achieved in accordance with the standards of completeness, Of KKM has beendetermined that 70, only about 12 students who were able to transcend the KKM and theremaining 10 students have not been able to achieve a predetermined KKM. In this regard,we need a method of learning that is able to facilitate students to gain experience of learningso as to provide greater opportunities for students to be able to develop in accordance withthe wishes and abilities. The purpose of this research is to improve student learning outcomesIPS SDN 011 Class IVB SDN 011 Bukit Gajah Kecamatan Ukui Kabupaten Pelalawan byimplementing cooperative learning model numbered heads together (NHT). This researchforms a classroom action research (PTK). From the research data is a daily test results ofstudents from elementary to UH I score has risen from an average of 60.78 into 77.5 18.09%.IPS learning outcome from the base score to UH II also increased, namely from 60.78 into83.28 by 37.02% and the teacher's activities each meeting has increased. From the firstmeeting in the first cycle of the activities of teachers percentage is 58.33% increased in thesecond cycle at the last meeting be 87.5%. Activities of students each meeting also increased.In the first cycle of the first meeting of student activity percentage was 58.33% and increasedin the second cycle last meeting to 83.33.